Sistem Pendukung Keputusan Pemilihan Rumpun Mata Kuliah di Program Studi dengan Metode Simple Additive Weighting - Al-fiqrie, Muhammad Biaggi; Sunarto, Dewiyani; Sukmaaji, Anjik (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2021)
One of the problems that often encountered in the environment of students in the Undergraduate Study Program is the selection of elective courses. Problems that arise ranging from students having confusion in the selection process to unstructured selection due to lack of guidelines. This can impact students to feel wrong in choosing and cause these courses to be unable to support the learning process. The existence of a class of courses that classify each subject based on the discipline of knowledge can be used to determine student criteria for the available class of courses. Student courses grades that have been taken and the student's interests will be grouped based on the class of courses. Later the value of these courses and student interests will be calculated using the Simple Additive Weighting (SAW) Method. The result will be directed to what elective courses are in the class of courses recommendation. A Decision Support System (DSS) was produced which aims to be a tool for students in selecting elective courses based on the results of previously calculated class of courses recommendations. With the selection based on a proven method, the selection becomes more structured.